2014
DOI: 10.1007/s11695-014-1350-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleeve Gastrectomy Is a Safe and Efficient Procedure in HIV Patients with Morbid Obesity: a Case Series with Results in Weight Loss, Comorbidity Evolution, CD4 Count, and Viral Load

Abstract: The sleeve gastrectomy was safe and effective with no consequences on CD4 counts and viral load in HIV-affected obese patients. It should be considered as a part of the treatment in morbidly obese HIV patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…Therapeutic drug monitoring of raltegravir in the setting of bariatric surgery is limited to two published cases. A 44‐year‐old woman with HIV infection who underwent sleeve gastrectomy was noted to have a raltegravir concentration of 372 ng/mL 16 hours following administration . The authors of this report cited a recommended raltegravir concentration of >150 ng/mL at 12 hours from administration.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Therapeutic drug monitoring of raltegravir in the setting of bariatric surgery is limited to two published cases. A 44‐year‐old woman with HIV infection who underwent sleeve gastrectomy was noted to have a raltegravir concentration of 372 ng/mL 16 hours following administration . The authors of this report cited a recommended raltegravir concentration of >150 ng/mL at 12 hours from administration.…”
Section: Resultsmentioning
confidence: 97%
“…Following bariatric surgery, the patient was noted to have an etravirine serum level of 1800 ng/mL at an unknown time period and a serum level of 1690 ng/mL at 16 hours from administration. According to the authors of this report, the recommended concentration of etravirine at 24 hours from administration is 300‐470 ng/mL . The patient was able to maintain viral suppression postoperatively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have demonstrated sub-therapeutic serum drug concentrations in HIV-infected patients after these procedures [7,8]. Regional delivery of oral ART medications to different portions of the upper gastrointestinal tract may influence systemic bioavailability [9], and the need for co-administered antacid therapy in the post-operative period may impair the gastrointestinal absorption of atazanavir [10].…”
Section: To the Editorsmentioning
confidence: 99%